Effectiveness of visual, auditory, and kinesthetic reading techniques on students’ reading comprehension: A sensory comparative study in the context of higher education - Marlia, Marlia; Quoc Si, Tran (BAHASTRA, 2025)
Reading interest in Indonesia remains low, negatively affecting students' reading comprehension and productive skills such as writing and speaking. Although various reading techniques have been introduced, their relative effectiveness remains uncertain. This study compares the effectiveness of four reading techniques—read-aloud, read-type, read-memorize, and read-write—on students' comprehension levels. Employing a quasi-experimental design with a posttest-only control group, this research involved 80 fifth-semester students of the Indonesian Language and Literature Education Study Program at FKIP Pasundan University in the 2023/2024 academic year. The participants were randomly assigned to four treatment groups, each receiving one of the reading techniques. Comprehension was assessed using a standardized test consisting of 30 multiple-choice and short-answer questions based on Bloom’s taxonomy, supplemented by observation of student behavior during reading. Data were analyzed using ANOVA and followed by Tukey HSD post-hoc testing. The findings revealed that the read-write group achieved the highest comprehension scores, followed by read-type, while read-aloud and read-memorize showed lower and statistically insignificant differences. Techniques involving kinesthetic activities—writing and typing—were more effective, likely due to deeper cognitive engagement from motor activity. This supports the levels of processing theory, which suggests that deeper encoding occurs through active manipulation of information. These results imply that incorporating kinesthetic reading strategies into learning activities can enhance reading comprehension. Practically, educators in higher education can integrate read-write and read-type strategies into coursework to improve critical reading skills and knowledge retention.